The Influence of Wordwall Learning Media on Fiqh Learning Outcomes of Students in Fiqh Subjects - Fikriansyah, Mohammad; Sutardi, Sutardi; Mustofa, Mustofa (EDU-RELIGIA : Jurnal Keagamaan dan Pembelajarannya, 2025)
The research model uses the CAR (class action research) in order to know the result on fiqh of the seventh grade using learning Wordwall because after using media learning Wordwall , the students obtained lessons completely in Islamic Junior High School Alhuda Brondong Academic Year 2023/ 2024. Population in this study were all students of 7th Grade Islamic Junior High School Alhuda Brondong Academic Year 2023/ 2024, as much 50 students. This research collected data by observation. From the data, before and after using learning Wordwall , or commonly called pre-test and post-test, which are tested using correlation with the standard product moment with the significance of 5 % and 95 % trust levels and significance rate 1 % and the trust level 99 %, The count is 0.955. While in rtabel with 50 respondents were known rtabel price 0.284 and 0.368. After being compared to rhitung, rhitung was greater than rtabel ( 0.284 < 0.955 <0.478 ), it means that Ho was rejected and Ha was accepted. In addition, in interpretation od judgements, correlation coefficient was found 0.955, which was between 0.80 -1.000 that was in the strong category.